Dynamic assessment of the electrocardiographic QT interval during citrate infusion in healthy Volunteers - Davis, T.M.E; Balbir, Singh; Choo, KE; Jamal, Ibrahim; Spencer, Janine L.; A St, John (British Medical Association, 1995)
To investigate changes in the electrocardiographic QT interval during rapidly induced, sustained hypocalcaemia in healthy volunteers. Serial rate corrected QT measurements were made during and after a variable rate trisodium citrate infusion designed to "clamp" the whole blood ionised calcium concentration 0.20 mmol/l below baseline for 120 min. 12 healthy teetotallers aged 19- 36 years who were not receiving medication known to influence calcium homoeostasis. Whole blood ionised calcium concentration and QaTc intervals (onset of the Q wave to T wave apex divided by the square root of the RR interval). Mean (SD) ionised calcium concentration decreased from 1.18 (0.03) mmol/l preinfusion to values close to target (0.98 mmol/l) between 10 and 120 min. The QaTc interval lengthened from a baseline of 0.309 (0.021) to a maximum 0.343 (0.024) s0.5 at 10 min before returning to a stable level from 15 to 120 min (0.334 (0.023) and 0.330 (0.023) s0.5 respectively). The change from baseline of both variables expressed as a ratio (delta QaTc/ delta [Ca2+]) was greater during rapid induction of hypocalcaemia (at 5 and 10 min) than at other times during and after the infusion (P < 0.02). The disproportionate prolongation of QaTc interval during prompt induction of hypocalcaemia suggests rate dependency which can be represented by a hysteresis relation between (ionised calcium, QaTc) coordinates. This finding may have clinical implications.